2016
DOI: 10.1094/pdis-04-15-0486-re
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of Goss’s Wilt of Corn and Epiphytic Clavibacter michiganensis subsp. nebraskensis from Inoculum Point Sources

Abstract: Goss’s wilt of corn, caused by Clavibacter michiganensis subsp. nebraskensis, has reemerged since 2006 as an economically important disease of corn in in the Midwestern United States. In 2012 and 2013, field plot studies were conducted with a pathogenic, rifampicin-resistant C. michiganensis subsp. nebraskensis isolate and a Goss’s wilt-susceptible corn hybrid to monitor epiphytic C. michiganensis subsp. nebraskensis population densities and the temporal and spatial spread of Goss’s wilt incidence originating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…C. nebraskensis survives epiphytically on symptomless maize leaves and it is possible that populations build up gradually over time in new areas before disease is detected (Eggenberger et al, 2016).…”
Section: Hos T R Ang E Of the Pathog Enmentioning
confidence: 99%
“…C. nebraskensis survives epiphytically on symptomless maize leaves and it is possible that populations build up gradually over time in new areas before disease is detected (Eggenberger et al, 2016).…”
Section: Hos T R Ang E Of the Pathog Enmentioning
confidence: 99%
“…Moreover, these alternate weeds likely enable the bacterium to become endemic to Iowa. Research from the Robertson lab has demonstrated that Cmn can be dispersed from point sources of inoculum such as a piece of Cmn-infested residue or an infected weed and colonize the leaves of corn seedlings season after emergence (Eggenberger et al 2016). This epiphytic population of Cmn on corn leaves gradually increases and disease occurs later in the season.…”
Section: Other Foliar Diseasesmentioning
confidence: 99%
“…With the increased demand for corn and corn products, there is an increased demand for more corn acres. This leads to tighter corn rotations and an increase in the incidence of corn diseases such as Goss’s wilt, which is triggered by the bacterial pathogen Clavibacter nebraskensis ( Cn ) [ 2 ]. This highly damaging Gram-positive bacterium grows as orange-colored colonies in agar culture media [ 3 , 4 ] and is part of a super-group of bacteria within the genus Clavibacter that infect a variety of other crops [ 3 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This highly damaging Gram-positive bacterium grows as orange-colored colonies in agar culture media [ 3 , 4 ] and is part of a super-group of bacteria within the genus Clavibacter that infect a variety of other crops [ 3 , 5 , 6 , 7 ]. Goss’s wilt has reached every state in the U.S. corn belt and every Canadian province with a significant corn production, and it has been on the rise since the adoption of glyphosate as the main method of weed control instead of conventional tillage [ 2 , 8 , 9 , 10 , 11 ]. Depending on where Cn enters the plant, it can cause either corn wilt or blight [ 8 , 9 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%